Assessing and Minimizing the Effect of Malaria on SARS-CoV-2 Serodiagnostics - Woodford, John; Sagara, Issaka; Kwan, Jennifer; Zaidi, Irfan; Dicko, Alassane; Duffy, Patrick E. (Frontiers in Tropical Diseases, 2021)
Malaria may affect the reliability of SARS-CoV-2 seroassay performance and limit understanding of SARS-CoV-2 epidemiology in malaria-endemic regions. We present our experience conducting SARS-CoV-2 serosurveillance in seasonal malaria-affected communities in Mali and discuss relevant literature regarding the effect of malaria on the performance of SARS-CoV-2 serodiagnostics, including approaches to minimize the effect of malaria-associated assay interference.